A qualitative evaluation of SMU’s peer helpers programme - KOH, Loon Beng Angela (Institutional Knowledge at Singapore Management University, 2021)
This study examines the impact of peer helper training in Singapore Management University (SMU) from personal interviews with 11 alumni peer helpers. The aims are to find a) new evidence of benefits and innovative practice that support peer helper learning, university life and employability and b) to enhance curriculum and training. All opinions in the sentiment analysis were positive. The content analysis revealed developing external partnerships, exploring certification and engaging in internationalisation to enhance curriculum, training and practice at the organisational level. At the programme level, the suggestions were to better relate peer helping to future readiness.